Munasabah QS. Al-Ma’idah 87-88 and QS. Al-Nahl 116 as the Moral Foundation for Combating Illegal Cigarettes and Illegal Thrifting - Nila Duriyatus Shofa; Masruhan; Abdulloh Umar Fauzi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
This study examines the phenomenon of illegal cigarettes and illegal thrifting in Indonesia through the lens of maqāşid al-Syarī’ah and the principle of religious moderation in the Qur’an. This study uses a library-based method with descriptive analysis of the interpretation of QS al-Mā’idah (5):87-88 and al-Naḥl (16):116, as well as Indonesian laws and regulations governing excise and trade, specifically Law No. 39/2007 on Excise and Law No. 7/2014 on Trade. The findings show that these two illegal practices are not only violations of positive law regarding the obligation to pay excise and the prohibition on importing used clothing, but also manifestations of “exceeding limits” and “prevarication in law” in economic activities, which are strongly condemned in the Qur’an. These practices clearly contradict the principles of maqāṣid al-Shari’ah, especially in protecting property (ḥifẓ al-Māl), life (ḥifẓ al-Nafs), and intellect (ḥifẓ al-’Aql), as they undermine state revenue, damage the national industrial structure, and increase health risks while normalizing fraud in society. In conclusion, eradicating illegal cigarettes and illegal thrifting practices is a concrete manifestation of religious moderation, because it rejects extremism in the form of ignoring Sharia norms and state laws, while affirming the synergy between Islamic values and the enforcement of fair fiscal and trade regulations to achieve economic justice and public welfare.